Socioeconomic Activities and Their Potential Impacts on Sustainable Food Safety and Livelihood Improvement in the Bahi Wetland, Central Tanzania - , Wodrick Philemon; , Julius S. Missanga; , Mary Ndimbo (Archives of Current Research International, 2018)
A cross-sectional assessment survey was conducted in five villages in central Tanzania to determine the impact of socioeconomic activities on food safety and livelihood improvement in the Bahi Wetland. The study, involving 209 randomly selected respondents, revealed crop farming, livestock keeping, fishing, beekeeping, salt and sand extraction, forest consumption, grass thatching, and eco-tourism as the main social economic activities in the wetland, but also that these were associated with unsuitable farming systems, overgrazing, illegal and overfishing, uncontrollable salt and sand extraction, deforestation from charcoal production as unsustainable practices with potential negative impacts on biological diversity of flora and fauna available in the wetland. The findings suggest that Bahi wetlands has enormous natural and socioeconomic potential, but conservation of wetland biodiversity has not been successful due to insufficient knowledge among communities around the wetland and lack of strong local institutional framework. Therefore, for sustainable management of wetland resources, the training and these frameworks should be well coordinated and implemented.